Colloidal interaction forces drive the selective separation of scheelite and calcite: a kinetics and AFM study - Wenjuan Sun; Guolei Liu; Ruolin Wang; Yujia Tian; Zhen Ye; Xujia Cao; Haisheng Han (Minerals Engineering, 2026)

Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

Intercropping with alfalfa or soybean alleviates the continuous cropping obstacles of yam by altering the rhizosphere community and its metabolites - Pengfei Zhang; Wanghui Guan; Lili Han; Xiaoli Hu; Ailing Xu; Ruolin Wang; Xiaomin Wang (Rhizosphere, 2026)

Metabolomic insights into flavonoid migration and bioactivity enhancement in Apocynum venetum tea during hot-water brewing - Syeda Wajeeha Gillani; Kuo Xu; Ping Li; Xueli Lu; Bo Wang; Lu Wang; Juying Wang; Guosheng Wang; Ruolin Song; Tingting Ren; Chen Meng; Yiqiang Li; et al. (Food Chemistry, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

Tailoring high-performance blend cementitious composites by co-recycling incineration fly ash, glass powder, and blast furnace slag - Yingying Xiong; Ruolin Zhao; Yan Xia; Liang Zhao; Bo Li; Atabaev F. Baxtiyarovich; Patryk Oleszczuk; Małgorzata Wiśniewska; Zengyi Ma; Lei Wang (Waste Disposal & Sustainable Energy, 2026)

Glycine-mediated steel slag upcycling: CO2 sequestration to functional materials - Ruolin Zhao; Lei Wang; Yan Xia; Junjie Yuan; Jianhua Yan (Journal of Environmental Chemical Engineering, 2026)

High-entropy heterogeneous design enables ultra-fatigue-resistant gel elastomers for multimodal sensing and intelligent human-machine interaction - Ruolin Wang; Baijie Cheng; Yexi Jin; Ying Xu; Jiajia Yang; Xihua Lu (Chemical Engineering Journal, 2026)

Electric vehicle manufacturers’ operation of charging stations: Higher range, greater benefits - Ruolin Yao; Shuai Ling; Qing Wang; Shiquan Zhong (Transportation Research Part D: Transport and Environment, 2026)

A mutation in CsBRP1, encoding a PHD-type domain-containing protein, causes semi-dwarfism in cucumber (Cucumis sativus L.) - Xiaoxu Han; Juan Yin; Xueying Jiao; Ruolin Hu; Yingjie Zhang; Fahang Chen; Biao Dong; Chunyan Cheng; Yuhui Wang; Chunhua Wang; Ji Li; Tao Wu; et al. (Theoretical and Applied Genetics, 2026)

The Pma-PABP4 gene, regulated by Pma-miR-1444, participates in Pinctada fucata gonad development - Ying Guo; Lirong Bai; Pei Wang; Tangrongjun Guo; Ruolin Zhu; Weiwei Chen; Xiuxiu Sang; Xianwei Fan; Dahui Yu (Animal Reproduction Science, 2026)

Cloning, tissue expression, and functional analysis of PfTDRD5, PfTDRD7-like, and PfTDRD9-like genes in pearl oyster Pinctada fucata - Tangrongjun Guo; Ying Guo; Pei Wang; Weiwei Chen; Ruolin Zhu; Lirong Bai; Dahui Yu (Journal of Oceanology and Limnology, 2026)

Biocontrol of Apple Valsa Canker by Bacillus sp. H12 and modulation of the apple seedlings microbiome - Ling Sun; Jianxin Gao; Yawen Tan; Yiting Xia; Ruolin Wang; Ruiqi Liu; Xinmei Zhang; Xia Yan; Lili Huang (Pesticide Biochemistry and Physiology, 2026)

Flame evolution behavior of syngas/air mixtures with a large range of equivalence ratios: Examination from the perspective of dynamics and thermal effects - Bin Su; Yuwei Wang; Zhenmin Luo; Ruolin Hao; Litao Liu; Shangyong Zhou; Tao Wang (Fuel, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Flammability limits and near-limit kinetic behaviors of multi-component syngas: A combined experimental and numerical study - Zhenmin Luo; Ruolin Hao; Bin Su; Lu Liu; Dinghan Li; Litao Liu; Shangyong Zhou; Tao Wang (Fuel, 2026)

Co-modulation of overall compressibility and conductive networks on individual sensing unit for high-performance flexible tactile sensors - Yifan Liu; Zheming Zhang; Xiao Xu; Fengming Hu; Ruolin Liu; Rongmei Wang; Ming Lei; Ziyi Dai; Bingpu Zhou (Chemical Engineering Journal, 2026)

Synergistic cytotoxicity of gymnodimine-A and okadaic acid in Caco-2 cells through coordinated disruption of calcium homeostasis and oxidative stress - Guixiang Wang; Jiangbing Qiu; Ruolin Wu; Aifeng Li; Ying Ji (Aquatic Toxicology, 2026)

Regulation of phenazine-1-carboxylic acid synthesis by hmgL in Pseudomonas chlororaphis and its role in restructuring plant microbiomes for disease resistance - Ruolin Wang; Boya Liu; Yutong Wu; Yu Wang; Xiaoyu Xia; Xia Yan; Lili Huang (Pesticide Biochemistry and Physiology, 2026)

Study of phenoxyethanol-citric acid biphasic pretreatment of sugarcane bagasse for enhanced enzymatic hydrolysis - Jili Liao; Ruize Wang; Xin Li; Ruolin Li; Danna Xie; Xiaoxue Zhao; Jing Wang; Caoxing Huang (Biomass and Bioenergy, 2026)

Widespread decline of gross primary productivity due to compound heat and drought in the Wei river Basin, China - Guangpo Geng; Ruolin Zheng; Tiantian Deng; Lei Zhang; Yousheng Wang; Zuxin He (Theoretical and Applied Climatology, 2025)

Adsorption of chlorogenic acid in aqueous solution of Chrysanthemum morifolium (Chuju) by walnut shell-derived biochar - Ying Gao; Nan Zhang; Xinran Xu; Ruolin Zhang; Jiahang Liu; Zongyao Qian; Xuelian Wang; Yunbin Qin (Food Chemistry, 2025)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

Per- and polyfluoroalkyl substances and platelet-related hematotoxicity: An integrated study of in silico, toxicological, and population evidence - Dihui Xu; Jie Xiang; Ruolin Qin; Zhijian Chen; Xiaofeng Wang; Peiwei Xu; Yitao Pan; Xinhan Zhang; Yan Wang; Ping Cheng; Yuan Chen; Dandan Xu; et al. (Journal of Hazardous Materials, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Discovery of selective ROCK2 inhibitors with free radical scavenging ability for the treatment of gouty arthritis - Ruolin Cao; Chuqiao Song; Zhe Wang; Bingqing Lv; Wei Xiao; Guoliang Chen; Xuefei Bao (Molecular Diversity, 2025)

The impact of increased water hardness on pollutant toxicity in freshwater aquatic organisms - Guangchao Shi; Jiawei Wang; Jianwei Yu; Sida Qin; Ruolin Liu; Dan Wu (Environmental Monitoring and Assessment, 2025)

Meta-analysis of electro-Fenton degradation efficiency: Unraveling the impacts of process parameters and cathode materials - Jiawei Wang; Guangchao Shi; Ruolin Liu; Shuhan Liu; Yuhan Zhang; Jianwei Yu; Dan Wu (Journal of Water Process Engineering, 2025)

Designing super-compatibility all-solid-waste binders for stabilization/solidification of Cr-contaminated soil - Ruolin Zhao; Yan Xia; Lei Ren; Huanyu Li; Binglin Guo; Liang Chen; Lei Wang (Journal of Hazardous Materials, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Effects of okadaic acid on Pyropia yezoensis: Evidence from growth, photosynthesis, oxidative stress and transcriptome analysis - Ruolin Wu; Jiangbing Qiu; Xianghai Tang; Aifeng Li; Yongmeng Yang; Xinyu Zhu; Xianyao Zheng; Wenke Yang; Guangyao Wu; Guixiang Wang (Journal of Hazardous Materials, 2025)

Recycling of MSWI fly ash into low-carbon supersulfated composites - Yan Xia; Zhenye Liu; Lei Wang; Ruolin Zhao; Gang Huang; Yaqian Shi; Yirou Zhou; Jianhua Yan (Chemical Engineering Journal, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Transcriptome analysis of the ovary and testis of the pearl oyster Pinctada fucata: Identification of genes and pathways involved in gonadal development - Ying Guo; Pei Wang; Ruolin Zhu; Tangrongjun Guo; Weiwei Chen; Xiuxiu Sang; Lirong Bai; Xianwei Fan; Dahui Yu (Animal Reproduction Science, 2025)

Ecological diversity and metabolic strategies of widespread Marinisomatota in global oceans - Shizheng Xiang; Jianyang Li; Zhen Chen; Ruolin Cheng; Liping Wang; Libo Yu; Guangshan Wei; Xiangyu Guan; Brandon R. Briggs; Gary King; Hongchen Jiang; Zongze Shao (Marine Life Science & Technology, 2025)

Lower toxicity of HFPO-DA compared to its predecessor PFOA to the earthworm Eisenia fetida: Evidence from oxidative stress and transcriptomic analysis - Ruolin Wu; Xiaole Wang; Jingwen Zhang; Chengbo Lu; Bing Li; Zhongkun Du; Jun Wang; Jinhua Wang; Yue Yang; Lusheng Zhu (Journal of Hazardous Materials, 2025)

Electron beam irradiation coupled ultrasound-assisted natural deep eutectic solvents extraction: A green and efficient extraction strategy for proanthocyanidin from walnut green husk - Heting Qi; Wanjia Fu; Yujie Liu; Junqing Bai; Ruolin Wang; Guangming Zou; Heyu Shen; Yingying Cai; Anwei Luo (Food Chemistry, 2025)

Dracocephalum Moldavica L.-derived carbon dots for effective periodontitis treatment via reprogramming energy metabolism in macrophages - Bo Zhang; Ruolin Ding; Xi He; Yifei Li; Zhongshan He; Jie Fang; Mengran Guo; Xinchun Wang; Zhihe Zhao; Xiangrong Song (Chemical Engineering Journal, 2024)

Heterojunction functionalized sodium alginate/carboxylated cellulose nanocrystals film enhancing sterilization performance for wound healing - Baijie Cheng; Ruolin Wang; Xinhao Wang; Nan Wang; Xiao-kun Ouyang (Carbohydrate Polymers, 2024)

Functional analysis of a rice 12-oxo-phytodienoic acid reductase gene (OsOPR1) involved in Cd stress tolerance - Longying Wu; Ruolin Wang; Mingyu Li; Zhiye Du; Yufan Jin; Yang Shi; Wenjun Jiang; Ji Chen; Yuan Jiao; Binhua Hu; Jin Huang (Molecular Biology Reports, 2024)

Occurrence and migration patterns of microplastics in different tidal zones of tourist beaches: A case study in the Bohai Bay, North China - Yutao Zuo; Yawen Ge; Ruolin Wang; Wanqiang Xu; Changhong Liu; Zixiao Guo; Shuo Wang; Huiyuan Jia; Yuecong Li (Journal of Environmental Management, 2024)

Characterization of MKK family genes and their responses to temperature stress and Vibrio parahaemolyticus infection in noble scallop Chlamys nobilis - Yetao Zeng; Ruolin Jiang; Jingwen Deng; Dewei Cheng; Weili Wang; Jianming Ye; Cheng He; Chuanxu Zhang; Hongkuan Zhang; Huaiping Zheng (Marine Environmental Research, 2024)

Electron beam and X-ray irradiation promote extraction of bioactive compounds from walnut green husk: Structural, physicochemical, and functional properties - Ruolin Wang; Heyu Shen; Junqing Bai; Guangming Zou; Yubing Shi; Jingfang Ao; Heting Qi; Yingying Cai; Anwei Luo (Food Bioscience, 2024)

Electron beam irradiation treatment driven structure-function relationships of walnut meal proteins and hydrolysates - Heyu Shen; Yubing Shi; Junqing Bai; Guangming Zou; Ruolin Wang; Huaide Xu; Jun Wang; Anwei Luo (Food Hydrocolloids, 2024)

Flame propagation dynamic characteristics and mechanisms of methane–syngas–air mixtures in a semi-enclosed duct - Lu Liu; Zhenmin Luo; Bin Su; Ruolin Hao; Tao Wang; Jun Deng; Fangzhi Song (Fuel, 2024)

Valorization of municipal solid waste incineration fly ash in low-carbon alkali-activated materials - Yan Xia; Zhenye Liu; Zhenhao Song; Ruolin Zhao; Jinpeng Wu; Lei Wang; Jianhua Yan (Chemical Engineering Journal, 2024)

Environmentally persistent free radicals on photoaging microplastics shortens longevity via inducing oxidative stress in Caenorhabditis elegans - Hui Li; Yongqi Jiang; Yulun Gu; Chao Chen; Jun Yu; Chen Wang; Chongli Shi; Ruolin Pan; Haibo Chen (Chemosphere, 2024)

Effectiveness of cawthorne-cooksey exercises in wallenberg syndrome-induced central vertigo - Na Ye; Zhao Ma; Xuyao Wang; Ruolin Liu; Xin Gu (Acta Neurologica Belgica, 2024)

An efficient photo-Fenton In2O3@FeIn2S4 composite catalyst for tetracycline degradation - Shengyu Jing; Jing Ren; Anhu Wang; Ruolin Cheng; Huagen Liang; Hai Liu; Fu Chen; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Sono-assembly of ellagic acid into nanostructures significantly enhances aqueous solubility and bioavailability - Wei Gu; Ruolin Kong; Shuyang Qi; Xuxi Cheng; Xuyi Cai; Ziyun Zhou; Shunan Zhang; Hongyu Zhao; Jinyun Song; Qinglian Hu; Huiwen Yu; Huangjin Tong; et al. (Food Chemistry, 2024)

Machine learning: An accelerator for the exploration and application of advanced metal-organic frameworks - Ruolin Du; Ruiqi Xin; Han Wang; Wenkai Zhu; Rui Li; Wei Liu (Chemical Engineering Journal, 2024)

Bi, K co-doped graphitic phase carbon nitride for efficient photocatalytic H2O2 production - Huagen Liang; Anhu Wang; Ruolin Cheng; Fu Chen; Palanisamy Kannan; Costas Molochas; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Provenance of surface dune sands in the Gurbantunggut Desert, northwestern China: Qualitative and quantitative assessment using geochemical fingerprinting - Baofeng Li; Qi Feng; Zaijun Li; Fei Wang; Chongwen Luo; Ruolin Li; Han Hu (Geomorphology, 2024)

Iron-rich industrial waste enhanced low-carbon radiation shielding functional composites - Yan Xia; Daquan Shi; Ruolin Zhao; Kunyang Yu; Minghao Liu; Hengjun Mei; Lei Xu; Yading Zhao; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Responses of plant immune system and rhizosphere soil microbiome to the elicitor BAR11 in Arabidopsis thaliana - Ruolin Wang; Yu Wang; Dandan He; Tiecheng Shi; Yanan Zhang; Shang Liu; Xia Yan; Lili Huang (Science of The Total Environment, 2024)

Responses of the intestinal microbiota to exposure of okadaic acid in marine medaka Oryzias melastigma - Yongmeng Yang; Aifeng Li; Jiangbing Qiu; Dongmei Gao; Chao Yin; Dongyue Li; Wenhui Yan; Hui Dang; Peiyao Li; Ruolin Wu; Lilin Han; Xiaoyun Wang (Journal of Hazardous Materials, 2024)

Study on coastal sediment budget imbalance in cells resulted from land cover change in the savanna desertification area, west Hainan Island (China) - Shilong Luo; Ruifang Jin; Jiaxin Wang; Xinhao Wang; Manyu Huang; Mengjiao Peng; Shuolei Xu; Ruolin Zhao (Journal of Sedimentary Environments, 2024)

Graphitic carbon nitride coupled with molybdenum selenide composite photocatalyst for tetracycline degradation - Huagen Liang; Anhu Wang; Ruolin Cheng; Fu Chen; Shengyu Jing; Angeliki Brouzgou; Panagiotis Tsiakaras (Journal of Environmental Chemical Engineering, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

The impact of water quality on the formation of halogenated benzoquinones and the adsorption efficiency by activated carbon - Yongjing Wang; Song Gao; Xinyu Yan; Songtao Wang; Ruolin Zhang; Yan Zhou; Lianhai Ren; Cheng Li (Journal of Environmental Sciences, 2024)

Efficient photocatalytic production of H2O2 and photodegradation of tetracycline by CdS/square tubular g-C3N4 S-scheme heterojunction photocatalyst - Shengyu Jing; Jingbo Zhao; Anhu Wang; Qiushi Ji; Ruolin Cheng; Huagen Liang; Fu Chen; Palanisamy Kannan; Angeliki Brouzgou; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Target-site and non-target-site based resistance to clodinafop-propargyl in wild oats (Avena fatua L.) - Yujun Han; Ying Sun; Hong Ma; Ruolin Wang; Yuning Lan; Haifeng Gao; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2023)

Selective fabrication of hydrophilic BiOCl deposition layer on bismuthinite surface for efficient molybdenite/bismuthinite separation - Shangyong Lin; Hongliang Zhang; Xiangsong Meng; Ruolin Wang; Wei Sun; Haisheng Han; Chenyang Zhang (Minerals Engineering, 2023)

TRIM21 of Micropterus salmoides exerts antiviral roles against largemouth bass ulcer syndrome virus - Zichao Peng; Caiyun Zhang; Baojie Yin; Yange He; Wenxian Li; Jinchao Wang; Jiaxin Xiao; Kaisong Peng; Chuanhe Bao; Ruolin Zhu (Fish & Shellfish Immunology, 2023)

Depression performance and mechanism of a novel reagent (Pb-starch) for calcite: Experimental and DFT study - Ruolin Wang; Hongliang Zhang; Wenjuan Sun; Haisheng Han (Minerals Engineering, 2023)

Conversion of agricultural waste to porous hydrochar for non-metallic activation of persulfate to phenol degradation via non-radical-dominated processes: Singlet oxygen and electron transfer - Jianhua Qu; Wanying Tong; Jun Zhang; Kaiyin Ye; Linsong Xiang; Ruolin Li; Di Wang; Zihe Chen; Qi Hu; Guangshan Zhang; Lei Wang; Ying Zhang (Journal of Cleaner Production, 2023)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Electronic nose application for detecting different odorants in source water: Possibility and scenario - Yongjing Wang; Xinyu Yan; Songtao Wang; Song Gao; Kai Yang; Ruolin Zhang; Mengshu Zhang; Moru Wang; Lianhai Ren; Jianwei Yu (Environmental Research, 2023)

Reproductive toxicity of microplastics in female mice and their offspring from induction of oxidative stress - Yingbing Zhang; Xiyue Wang; Yifan Zhao; Jianglin Zhao; Tong Yu; Yupei Yao; Ruolin Zhao; Ruiluan Yu; Jun Liu; Jianmin Su (Environmental Pollution, 2023)

Photocatalytic CO2 cycloaddition over highly efficient W18O49-based composites: An economic and ecofriendly choice - Ruolin Cheng; Anhu Wang; Shuxun Sang; Huagen Liang; Shiqi Liu; Panagiotis Tsiakaras (Chemical Engineering Journal, 2023)

The effect of TiO2NPs on cloransulam-methyl toxicity to earthworm (Eisenia fetida) - Ruolin Wu; Hunan Liu; Chengbo Lu; Kaixuan Hou; Xiaole Wang; Jun Wang; Zhongkun Du; Bing Li; Lusheng Zhu; Jinhua Wang (Chemosphere, 2023)

Chemical weathering evidence for East Asian Summer Monsoon rainfall variability in the upper reaches of the Yellow River since the Early Pleistocene - Baofeng Li; Qi Feng; Fei Wang; Zaijun Li; Xin Wang; Ruolin Li; Weiyu Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Let-7c-5p down-regulates immune-related CDCA8 to inhibit hepatocellular carcinoma - Wanjin Chen; Haibo Wang; Yuanlong Shen; Shouwen Wang; Deng Liu; Hongchuan Zhao; Guobin Wang; Fan Huang; Wei Wang; Ruolin Wu; Liujin Hou; Zhenghui Ye; et al. (Functional & Integrative Genomics, 2023)

An R2R3-MYB FtMYB11 from Tartary buckwheat has contrasting effects on abiotic tolerance in Arabidopsis - Qian Chen; Lu Peng; Anhu Wang; Lingzhi Yu; Yu Liu; Xinrong Zhang; Ruolin Wang; Xiaoyi Li; Yi Yang; Xufeng Li; Jianmei Wang (Journal of Plant Physiology, 2023)

Leaching of heavy metal(loid)s from historical Pb–Zn mining tailing in abandoned tailing deposit: Up-flow column and batch tests - Yuan Yao; Lizhi Tong; Ruolin Zhao; Qianhui Wang; Jinli Qiu; Fenghe Wang; Jining Li; Yifan Yan; Yue He; Shuqin Li (Journal of Environmental Management, 2023)

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Early warning model for death of sepsis via length insensitive temporal convolutional network - Minghui Gong; Jingming Liu; Chunping Li; Wei Guo; Ruolin Wang; Zheng Chen (Medical & Biological Engineering & Computing, 2022)

New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Ruolin Li; Yu Guo; Chuanxin Qin; Shuo Zhang; Dongping Ji; Hui Zhang; Jing Wang; Naiqian Zhao (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs ( P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.

Induced sputum metabolomic profiles and oxidative stress are associated with chronic obstructive pulmonary disease (COPD) severity: potential use for predictive, preventive, and personalized medicine - Tao Zhu; Shanqun Li; Jiajia Wang; Chunfang Liu; Lei Gao; Yuzhen Zeng; Ruolin Mao; Bo Cui; Hong Ji; Zhihong Chen (EPMA Journal, 2020)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease, and metabolomics plays a hub role in predictive, preventive, and personalized medicine (PPPM) related to COPD. This study thus aimed to reveal the role of induced sputum metabolomics in predicting COPD severity. In this pilot study, a total of 20 COPD patients were included. The induced sputum metabolites were assayed using a liquid chromatography-mass spectrometry (LC-MS/MS) system. Five oxidative stress products (myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), neutrophil elastase (NE), and 8-iso-PGF2α) in induced sputum were measured by ELISA, and the metabolomic profiles were distinguished by principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLS-DA). The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used for pathway enrichment analysis, and a significant difference in induced sputum metabolomics was observed between moderate and severe COPD. The KEGG analysis revealed that the glycerophospholipid metabolism pathway was downregulated in severe COPD. Due to the critical role of glycerophospholipid metabolism in oxidative stress, significant negative correlations were discovered between glycerophospholipid metabolites and three oxidative stress products (SOD, MPO, and 8-iso-PGF2α). The diagnostic values of SOD, MPO, and 8-iso-PGF2α in induced sputum were found to exhibit high sensitivities and specificities in the prediction of COPD severity. Collectively, this study provides the first identification of the association between induced sputum metabolomic profiles and COPD severity, indicating the potential value of metabolomics in PPPM for COPD management. The study also reveals the correlation between glycerophospholipid metabolites and oxidative stress products and their value for predicting COPD severity.

Isotopic fingerprinting of dissolved iron sources in the deep western Pacific since the late Miocene - Ruolin Liu; Bai Guo; Maoyu Wang; Weiqiang Li; Tao Yang; Hongfei Ling; Tianyu Chen (Science China Earth Sciences, 2020)

Pleiotropic QTL influencing spikelet number and heading date in common wheat (Triticum aestivum L.) - Zhaoyan Chen; Xuejiao Cheng; Lingling Chai; Zihao Wang; Dejie Du; Zhihui Wang; Ruolin Bian; Aiju Zhao; Mingming Xin; Weilong Guo; Zhaorong Hu; Huiru Peng; et al. (Theoretical and Applied Genetics, 2020)

Precipitation recycling using a new evapotranspiration estimator for Asian-African arid regions - Ruolin Li; Chenghai Wang (Theoretical and Applied Climatology, 2020)

Dissection of genetic factors underlying grain size and fine mapping of QTgw.cau-7D in common wheat (Triticum aestivum L.) - Zhaoyan Chen; Xuejiao Cheng; Lingling Chai; Zhihui Wang; Ruolin Bian; Jiang Li; Aiju Zhao; Mingming Xin; Weilong Guo; Zhaorong Hu; Huiru Peng; Yingyin Yao; et al. (Theoretical and Applied Genetics, 2020)

NGF protects bone marrow mesenchymal stem cells against 2,5-hexanedione-induced apoptosis in vitro via Akt/Bad signal pathway - Qi Wang; Ruolin Chen; Cong Zhang; Inam-u-llah; Fengyuan Piao; Xiaoxia Shi (Molecular and Cellular Biochemistry, 2019)

Anaerobic digestion of tobacco stalk: biomethane production performance and kinetic analysis - Lyu Li; Ruolin Wang; Zhenlai Jiang; Wanwu Li; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2019)

Changes in precipitation recycling over arid regions in the Northern Hemisphere - Ruolin Li; Chenghai Wang; Di Wu (Theoretical and Applied Climatology, 2018)